1998
DOI: 10.1109/8.686777
|View full text |Cite
|
Sign up to set email alerts
|

Application of the fast far-field approximation to the computation of UHF pathloss over irregular terrain

Abstract: The recent availability of fast numerical methods has rendered the integral-equation approach suitable for practical application to radio planning and site optimization for UHF mobile radio systems. In this paper, we describe a conceptually simple scheme for the efficient computation of UHF radial propagation loss over irregular terrain, which is based on the fast far-field approximation. The method is substantially faster than conventional integral-equation (IE) solution techniques. The technique is improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 17 publications
0
24
0
2
Order By: Relevance
“…It is also worth mentioning that, the empirical methods are run on the surfaces Green's function with measurement data or Hata model have been presented [18], [20]. However, those IE methods do not dicretize the surface profile as much as FBSA does and also they use additional approximations, such as neglecting the backscatter.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth mentioning that, the empirical methods are run on the surfaces Green's function with measurement data or Hata model have been presented [18], [20]. However, those IE methods do not dicretize the surface profile as much as FBSA does and also they use additional approximations, such as neglecting the backscatter.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…As in the previous case, this method remains computationally complex, although a parallel implementation of the method allows the solution of some practical problems in the VHF band. A more efficient solution can be found in [20], where the fast far field approximation (FAFFA) was introduced and modified in an integral equation formulation for the terrain propagation problem. The FAFFA reduces the operational cost of the previous IE methods from O(N 2 ) per iteration to O(N 4/3 ).…”
Section: Integral Equation Based Methods For Terrain Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…This could become a serious constraint to many propagation applications. They also observed that a number of time-saving measures [5] could be developed to deal with this aspect of integral equations, even though this was not within the goals of their paper.…”
Section: Introductionmentioning
confidence: 92%
“…Backscattering could be Manuscript received April 6, 1998 explicitly accounted for and the whole computation took a matter of seconds on a modest computational resource such as an HP workstation. The fast far-field algorithm (FAFFA) [9], which is related to the well-documented fast multiple method [10], was combined with the Green's function perturbation method (GFPM) [11], [12] and offers large computational savings over a wider range of problems than those amenable to rapid NBS solution. Though not as fast as the NBS, the FAFFA was further specialized (via the incorporation of certain assumptions, described in Section II, about the problem geometry and incident field) into an extremely rapid scheme namely the tabulated interaction method (TIM) [13] which, for terrain problems, combined the robustness of the FAFFA with the speed of the NBS.…”
Section: Introductionmentioning
confidence: 99%